2014
DOI: 10.1080/00063657.2014.940838
|View full text |Cite
|
Sign up to set email alerts
|

A study of nesting sparrowhawksAccipiter nisususing video analysis

Abstract: Capsule Chick age influenced female prey size and the provisioning rate of each parent while rainfall increased female brooding in a single sparrowhawk territory in Edinburgh. Aims To study the details of prey delivery, female brooding and the factors affecting chick mortality in a single sparrowhawk territory in Edinburgh. Methods Video footage collected from a sparrowhawk nest in the Royal Botanic Garden Edinburgh in 2011 and 2012 was used to record the occurrence and size of prey deliveries by each parent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(57 reference statements)
0
2
1
Order By: Relevance
“…Most likely this reflected the chicks being provisioned away from the view of the webcam rather than an actual decrease. Similarly increased provisioning of nestling raptors is widespread where prey availability is sufficient to meet the chicks' demand, either via increased rates of delivery or the delivery of larger prey (e.g., Watts 2014). At their highest, the rates of prey delivery we observed are slightly lower than Laing's (1985) estimate of 9.6 deliveries per day across the nestling period for Merlin nests in Denali National Park, Alaska.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Most likely this reflected the chicks being provisioned away from the view of the webcam rather than an actual decrease. Similarly increased provisioning of nestling raptors is widespread where prey availability is sufficient to meet the chicks' demand, either via increased rates of delivery or the delivery of larger prey (e.g., Watts 2014). At their highest, the rates of prey delivery we observed are slightly lower than Laing's (1985) estimate of 9.6 deliveries per day across the nestling period for Merlin nests in Denali National Park, Alaska.…”
Section: Discussioncontrasting
confidence: 60%
“…Attendance declines substantially once the nestlings reach thermoregulatory independence (Holthuijzen 1990, Katzenberger et al 2015, Keeley and Bechard 2017. The species' body size and rate of development modify the chicks' time to homeothermy and the associated drop in the adults' brooding, but brooding varies in response to weather such as rain and abnormally cold or warm temperatures (Watts 2014, Katzenberger et al 2015. Our observations align with expectations in terms of parental roles during the nestling phase, but the suggestion that Merlins attain homeothermy by D7 (Warkentin et al 2005) may be too optimistic, given the continued brooding past D7 that we observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation